Analisis Modal Sosial Terhadap Penerapan Sistem Jaminan Produk Halal (SJPH) pada Pelaku Usaha di Pantai Lon Malang - Ulimas, Ria Vinola; Rahayuningsih, Eni Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the role of social capital in the implementation of the Halal Product Assurance System (SJPH) among businesses in Lon Malang Beach. Social capital represents the characteristics of social organizations, such as networks, norms, and social trust, which facilitate coordination and mutually beneficial cooperation. SJPH is a quality management system that ensures the produced goods meet halal standards. This research employs a qualitative method. Data were collected through observation, interviews, and documentation. The results of the study indicate that businesses in Lon Malang Beach are in the process of implementing halal product assurance after attending socialization sessions organized by the Village-Owned Enterprises (BUMDes). They have started using materials uncontaminated by non-halal substances. If using animals as raw materials, the slaughtering process must adhere to Islamic Sharia law. Additionally, 19 individuals have obtained a Business Identification Number (NIB) as a requirement for applying for halal certification. The implementation of SJPH is influenced by strong social capital between business operators and BUMDes, which provides assistance and guidance in the halal certification process. This robust social capital is reflected in the norms, trust, networks, and reciprocal relationships that are mutually beneficial between the businesses and BUMDes. Although they do not yet possess halal certificates, the Madurese community has a high awareness of halal practices, as these have been taught from a young age by figures such as Bhuppa,' Bhâbhu', Ghuru, and Rato (Father, Mother, Government Leader). However, the ability to obtain halal certification is still low due to the limited knowledge about the certification registration process.